Willingness and Perceptions Regarding COVID-19 Vaccine Booster Dose in Pakistani Vaccinated Population: A Cross-Sectional Survey - Abdul Moeed; Hala Najeeb; Arisha Saleem; Muhammad Sohaib Asghar; Hania Mansoor Rafi; Abdullah Khan Khattak; Zoha Bilal; Binyam Tariku Seboka (Frontiers Media S.A., 2022)
ObjectivesThis study was conducted to evaluate COVID-19 vaccine booster dose willingness and identify predictors and factors of willingness and hesitance in the vaccinated population of Pakistan.MethodsA cross-sectional web-based survey was undertaken between January and February 2022 to highlight the public perceptions regarding the COVID-19 booster dose and evaluate the willingness to get the additional dose. Demographic information and booster dose willingness were recorded through the questionnaire. Additionally, a 5-point Likert scale was employed to explore fears and beliefs regarding COVID-19 vaccinations. Univariate and multivariate regression was performed to identify booster dose willingness and hesitance factors.ResultsOf the 787 respondents, 69.6% were females, 75.3% fell in the 18-30 years age group, 53.5% were university students or had a Bachelor's degree. Overall, a 77.8% booster dose willingness was reported. Participants showed absence or low fear levels associated with a booster dose (47.3%). 60.1% agreed it was safe to receive an additional vaccine dose, with 44.1% agreeing that boosters are effective against coronavirus variants. Independent predictors of willingness included the absence of comorbidities, whereas not being willing to pay for the booster dose was a predictor of hesitance.ConclusionThis study showed a suboptimal willingness level of booster dose uptake among the vaccinated Pakistani population. Public health policymakers must undertake necessary awareness campaigns to strategize vaccination drives and dispel myths.